PHYTOCHEMICAL SCREENING AND RENAL EFFECTS OF ETHANOLIC EXTRACT OF ERIOBOTRYA JAPONICA FRUITS AND SEEDS IN ALLOXAN INDUCED DIABETIC RATS - Shafi, Sabeeha; Tabassum, Nahida (International Journal of Current Pharmaceutical Research, 2018)
Objective: The main aim of the present study was to evaluate the phytochemical constituents, and renal effects of the ethanolic extract of the fruits and seeds of Eriobotrya japonica, commonly called as Loquat in Kashmir. So far, no such study was carried in Kashmir. Methods: Phytochemical screening involved the standard procedures. Diabetes was induced in albino rats using alloxan monohydrate (120 mg/kg b. w) given i. p prepared in sterile saline. Rats were divided into 8 groups of 6 rats in each group. The ethanolic extract of Eriobotrya japonica fruits were given in doses of 50 mg/kg, 100 mg/kg, and 200 mg/kg b. w. whereas the ethanolic extract of Eriobotrya japonica deeds were given in doses of 100 and 200 mg/kg b.w. The renal effects were determined by estimating the kidney function tests i.e., serum urea levels, serum creatinine levels and serum total proteins. The effects were compared with the normal control rats. Results: Phytochemical screening revealed the presence of some useful phytoconstituents. alkaloids, glycosides and flavonoids in both extracts. The renal effects showed changes in alloxan-induced diabetic rats when treated with the ethanolic extract of the fruit and seeds of Eriobotrya japonica. Conclusion: The ethanolic extract of E. J units and seeds have some useful Phytonstihut and there are some renal changes by the ethanolic extraction of E. B. F and S when admi to alloxaun inderced diabetic rats.Â 